Modern dynamics of water levels and their flood rises in the upper reaches of the Prut River within the Chornohora Landscape (Ukrainian Carpathian) - Карабінюк М. М.; Гнатяк І. С.; Буряник О. О.; Гостюк З. В.; Карабінюк Я. В. (Київський національний університет імені Тараса Шевченка, 2021)
This article presents the results of an analysis of modern water levels in the upper reaches of the largest river, the Prut, in the mountain landscape of Chornohora, for the period from 2010 to 2019, based on data from our long-term hydro-meteorological observations at the Landscape Monitoring Laboratory of Ivan Franko National University. The studied river is characterized by a dense river network, a peculiar hydrological regime and periodic formation of heavy floods, as well as the presence in its basin of valuable landscape complexes and environmental facilities, high landscape diversity and recreational and tourist potential, which determines the relevance of this study. As a result of the study, the peculiarities of the formation and modern features of the hydro network of the Prut river basin were established, its heterogeneity in the mid-mountain and high-mountain landscape tiers was characterized. It is established that during the period 2010-2019 in the upper reaches of the Prut River there was an increase in river water levels, as well as identified the main factors and their impact on current changes in the hydrological regime of the river. The annual changes in the water level in the upper reaches of the Prut River for the period 2010-2019 were also analyzed and it was found that its mountainous nature causes high dynamics of river water levels at different times of the year and in certain months. It was important to identify the relationships between their indicators and the characteristics of the annual distribution of precipitation and snowmelt during studying the annual cycles of water level fluctuations. Particular attention is paid to the study of the formation and spread of floods as the most dangerous hydrological phenomenon of the upper reaches of the Prut River, characterized by a sharp rise in water levels, high erosion capacity, etc. The study found that more than 75 % of floods occur during the spring snowmelt in April and May where the average daily river water levels usually do not exceed 60-70 cm. The analysis of flood rises in terms of years and months shows that the most severe catastrophic floods are formed in November-December due to heavy rains, which cause the formation of powerful destructive water flows and catastrophic growth of river water levels over 90-100 cm. The total annual number of flood rises in the Prut River was also analyzed according to certain categories of indicators (over 60 cm, 70 cm, etc.) and it was found that the total number of floods in the upper reaches of the river is increasing.

У статті представлені результати аналізу сучасної динаміки рівнів вод верхів’я найбільшої річки гірського ландшафту Чорногора – річки Прут, за період з 2010 по 2019 роки, що ґрунтується на даних власних багаторічних гідро-метеорологічних спостережень на базі Лабораторії ландшафтного моніторингу Чорногірського географічного стаціонару Львівського національного університету імені Івана Франка. Досліджувана річка характеризується густою річковою мережею, своєрідним гідрологічним режимом та періодичним формуванням потужних паводків. Також характеризується наявністю у її басейні цінних ландшафтних комплексів та природоохоронних об’єктів, високим ландшафтним різноманіттям і рекреаційно-туристичним потенціалом, що обумовлює актуальність цього дослідження. У результаті проведеного дослідження встановлені особливості формування та сучасні риси гідромережі басейну р. Прут, охарактеризовано її неоднорідність у середньогірному і високогірному ландшафтних ярусах та ін. Встановлено, що за період 2010-2019 років у верхів’ї р. Прут спостерігалося збільшення рівнів річкових вод, а також визначені основні фактори та їхній вплив на сучасні зміни у гідрологічному режимі річки. Проаналізовано річні зміни рівнів води у верхів’ї р. Прут за період 2010-2019 років та встановлено, що її гірський характер обумовлює високу динамічність рівнів річкових вод у різних порах року та окремих місяцях. При вивченні річних циклів коливання рівнів вод, важливим було виявлення взаємозв’язків між їхніми показниками та особливостями річного розподілу опадів і сніготаненням. Особливу увагу приділено вивченню особливостей утворення та поширення паводків – найнебезпечнішого гідрологічного явища верхів’я р. Прут, що характеризується різким підвищенням рівнів вод, високою ерозійною здатністю та ін. Визначено, що понад 75 % паводків формуються під час весняного сніготанення у квітні та травні, при яких середньодобові показники рівнів річкових вод, зазвичай, не перевищують 60-70 см. Проведений аналіз паводкових підйомів рівнів вод у розрізі років та місяців свідчить, що найпотужніші паводки катастрофічного характеру формуються у листопаді-грудні внаслідок зливових дощів, які зумовлюють утворення потужних руйнівних водних потоків та катастрофічне зростання рівнів річкових вод понад 90-100 см. Також проаналізована сумарна річна кількість паводкових підйомів рівнів води у р. Прут за окремими категоріями показників (понад 60 см, 70 см і т.д.) та встановлено, що загальна кількість паводків у верхів’ї річки збільшується.
Сучасна динаміка рівнів вод та їх паводкових підйомів у верхів’ї річки Прут у межах ландшафту Чорногора (Українські Карпати)
Keywords: гідрологічний режим; рівень річкових вод; гідромережа; паводок; річковий басейн; ландшафт Чорногора; hydrological regime; river network; river water level; flood; river basin; Chornohora Landscape